CALCULATION OF THE ECONOMIC EFFICIENCY OF THE TECHNOLOGY WHEN OBTAINING SAFFLOWER OIL - Akramova Rano Ramizitdinovna; Muhammedova Shoxista; Mirahmadov Jahongir (Journals Park Publishing, 2022)
The article discusses the results of economic indicators in the production of non-traditional vegetable safflower oil from local raw materials of the Republic of Uzbekistan.
Keywords: safflower oil; cake; economic calculation